Modernism and Style - Hutchinson, B. author. aut Link
XX, 291 p.
Keywords: Modernism is fundamentally determined by its relationship to its own notions of style: oscillating between the poles of 'pure' style and 'purely' style, this traces the stylistic self-conceptualization of modernism from Schopenhauer and Flaubert in the 1850s, through Nietzsche and the symbolists in the 1880s, to the high modernists of the 1920s.